Salvage therapy containing sorafenib and donor lymphocyte infusion is associated with improved outcomes for FLT3 wild-type acute myeloid leukemia relapsing after allogeneic hematopoietic stem cell transplantation - Zhonghui Jiang; Ya Zhou; Yuxin Bai; Fang Dai; Menglin Fan; Tian Zhang; Danian Nie; Yunxin Zeng; Yirong Jiang; Ping Zhu; Zhiping Fan; Na Xu; et al. (Biomarker Research)
Abstract Background There is no established standard treatment for acute myeloid leukemia (AML) patients with FLT3 wild-type relapsing after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Multi-kinase inhibitor sorafenib has been widely explored in the treatment of AML patients with FLT3 internal tandem duplication (FLT3-ITD) mutations. Some studies have revealed that the addition of sorafenib to standard chemotherapy could improve outcomes in newly diagnosed AML regardless of FLT3 status. However, the application of sorafenib in FLT3 wild-type AML patients experiencing relapse after allo-HSCT remains minimally investigated. Methods We retrospectively compared the effects of conventional treatment combined with or without sorafenib on the outcomes of these patients. The study mainly focused on the treatment response of salvage therapy and survival. Results Sixty-two AML patients with FLT3 wild-type who relapsed after allo-HSCT were enrolled in this study, including 38 with sorafenib and 24 without sorafenib. Fifty patients received 68 doses of donor lymphocyte infusion (DLI). The rate of composite complete remission was 65.8% in the sorafenib group, compared with 29.2% in the non-sorafenib group (P = 0.005). With a median follow-up of 13.2 months (IQR, 3.2–43.5) after relapse, the 2-year overall survival (OS) was 47.4% (95%CI, 33.9%-66.2%) and 16.7% (6.8%-40.8%) in the sorafenib and non-sorafenib groups (P = 0.006). The 2-year event-free survival (EFS) was 44.7% (31.4%-63.7%) and 16.7% (6.8%-40.8%) in the two groups (P = 0.012). Multivariable analysis revealed that salvage therapy including sorafenib was the protective factor for longer OS and EFS (HR = 0.395, 95% CI: 0.209–0.746, P = 0.004; HR = 0.406, 95% CI: 0.218–0.754, P = 0.004). The incidences of acute graft-versus-host disease (GVHD) and chronic GVHD were similar between the two groups (P = 0.806, P = 0.908). Conclusion Our results suggest that salvage therapy including sorafenib and DLI is associated with improved outcomes for AML patients with FLT3 wild-type relapsing after allo-HSCT.